Name Wheel Application through Basic ABC Games for Children's Language Development : - Lestari, Astri; Pansuri, Fitria Farhani; Sunarsih, Dewi; Fitria, Nila (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
Early childhood is an important period for language development. Indonesia, which is still a developing country, still needs to make efforts to improve children's language skills. This research aims to describe the application of the Name Wheel through Basic ABC Games for Children's Language Development. Using a qualitative descriptive approach with participants aged 4 - 5 years, totaling 12 children consisting of 6 boys and 6 girls who were directly involved in the learning. The results of the research show that the development components of language comprehension abilities, in general, begin to grow based on observations made after children play the Basic ABC game using wheel names. A child's ability to pay attention to and understand the instructor's instructions after the spinning wheel stops is one sign that the child has improved their understanding of language. Apart from that, children can also understand the rules when playing the game. It is hoped that this research can help teachers to always innovate in designing learning for children based on children's developmental achievements. Keywords: children's language development, application of the name wheel, basic ABC games References: Elizabeth, H. (1978). Perkembangan Anak. Erlangga. Febryana, E. (2019). Peningkatan Keterampilan Berbahasa Melalui Permainan Tradisional Abc Lima Dasar Pada Pembelajaran Tematik Di Kelas 1 Ar-Rahman MI Ma’arif Setono Tahun Pelajaran 2018/2019. Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam Negeri Ponorogo. Fitria, N., Amelia, Z., & Nurfadilah, N. (2022). Pengaruh Flashcard Path To Literacy terhadap Kemampuan Literasi Baca Tulis. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(5), 4039–4048. https://doi.org/10.31004/obsesi.v6i5.2236 Hasibuan, R., & Rakhmawati, N. I. S. (2021). Information & Communication Technology in Shaping Character During the Covid-19 Pandemic. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(2), 1930–1942. https://doi.org/10.31004/obsesi.v5i2.594 Ita, E., Wewe, M., & Go.o, E. (2020). Analisis Perkembangan Kemampuan Bahasa Anak Kelompok A Taman Kanak-Kanak. Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 3(2), 174–186. https://doi.org/10.24042/ajipaud.v3i2.7317 Jurkic, A., Halliday, S. E., & Hascher, T. (2023). The relationship of language and social competence of preschool- and kindergarten-age single and dual language learners in Switzerland and Germany. Early Childhood Research Quarterly, 64(February), 72–83. https://doi.org/10.1016/j.ecresq.2023.02.003 Kandow, T., Dengo, S., & Mambo, R. (2021). Strategi Dinas Perpustakaan Daerah dalam Meningkatkan Minat Baca Masayarakat Kabupaten Bolaang Mongondow Timur. Jurnal Administrasi Publik, 7(109), 34–43. https://ejournal.unsrat.ac.id/v3/index.php/JAP/article/view/35345 Kementrian Pendidikan Nasional RI. (2014). Standar Nasional Pendidikan Anak Usia Dini No 137 Tahun 2014. Peraturan Menteri Pendidikan Dan Kebudayaan Republik Indonesia, 1–76. https://portaldik.id/assets/upload/peraturan/PERMEN KEMENDIKBUD Nomor 137 Tahun 2014 STANDAR NASIONAL PENDIDIKAN ANAK USIA DINI.pdf Khomsiyatun, U. (2019). Pola Pengembangan Literasi Bahasa Pada Anak Studi Kasus Di PAUD Wadas Kelir. JUrnal Metabasa, 1, 29–34. Kuder, S. J., & Hasit, C. (2022). Enhancing Literacy for All Students. Merrill/Prentice Hall. Luthfillah, N., Yusuf Muslihin, H., & Rahman, T. (2022). Analisis Pengembangan Bahasa Dan Kognitif Anak Usia Dini Melalui Metode Bernyanyi. Early Childhood: Jurnal Pendidikan, 6(1), 1–13. https://doi.org/10.35568/earlychildhood.v6i1.2128 Mulyani, N. (2016). Permainan Tradisional Anak Indonesia. Diva Press. Munawar, M., Prasetyo, A., & Pusari, R. W. (2013). Pengembangan Model Pembelajaran Inovatif Melalui Pendekatan In House Training Berbasis Kearifan Budaya Lokal. Jurnal Penelitian PAUDIA, 2(1), 1–13. Muzarkasi, M. (2016). Penerapan Permainan ABC 5 Dasar Dalam Peningkatan Kemampuan Membaca Permulaan Pada Siswa Kelas 1 SDN 1 Kuripan Utara Tahun Ajaran 2015/2016, (2016). Universitas Mataram. Nugraha, D., & Octavianah, D. (2019). Diskursus Literasi Abad 21 di Indonesia. JPE (Jurnal Pendidikan Edutama), 6(1), 59–64. Nurdiansyah. (2019). Media Pembelajaran Inovatif. UMSIDA Press. Pakpahan, R., & Fitriani, Y. (2020). Analisa Pemafaatan Teknologi Informasi Dalam Pemeblajaran Jarak Jauh Di Tengah Pandemi Virus Corona Covid-19. JISAMAR (Journal of Information System, Applied, Management, Accounting and Researh), 4(2), 30–36. Pamungkas, A. H. (2018). Pemanfaatan Experiential Learning Untuk Pembelajaran Berbasis Teknologi Pada Pembelajaran Anak Usia Dini. Jurnal Ilmiah Teknologi Pendidikan, 6(2), 25–45. http://ejournal.unp.ac.id/index.php/e-tech/article/view/101366 Permendikbud, 137. (2014). Peraturan Menteri Pendidikan dan Kebudayaan Republik Indonesia, “Peraturan Menteri Pendidikan Dan Kebudayaan Republik Indonesia Nomor 137 Tahun 2014. Menteri Pendidikan dan Kebudayaan Republik Indonesia. https://portaldik.id/assets/upload/peraturan/PERMEN KEMENDIKBUD Nomor 137 Tahun 2014 STANDAR NASIONAL PENDIDIKAN ANAK USIA DINI.pdf. Prayitno, P. (2019). Pembelajaran batik tetes lilin sebagai alternatif teknik membatik sederhana pada mahasiswa PAUD. Jurnal Pendidikan Anak, 8(1), 38–47. https://doi.org/10.21831/jpa.v8i1.26678 Priyanto, A. (2014). Pengembangan Kreativitas Pada Anak Usia Dini Melalui Aktivitas Bermain. Journal.Uny.Ac.Id, 02. Rabiah, S. (2020). Languanges as a Tool for Communication and Cultural Reality Discloser. 1–11. http://slubdd.de/katalog?TN_libero_mab216782845 Rahman, A., Marpaung, E. P., Lubis, H. F., Sinaga, M. N. F., & Nawawi, Z. M. (2021). Pengembangan Literasi Dasar dalam Meningkatkan Minat Membaca dan Menulis pada Anak Usia Dini di Perumahan Indah Permai Desa Petatal. Edumaspul: Jurnal Pendidikan, 5(1), 674–680. https://doi.org/10.33487/edumaspul.v5i2.2009 dan P. Suryani. (2018). Media Pembelajaran Inovatif dan Pengembangannya. PT. Remaja Rosdakarya Offset. Saputra, R. (2023). Cara Menggunakan Aplikasi “Spinning Wheel Names” Agar Guru Semakin Kreatif dalam Mengajar. GuruInovatif. https://guruinovatif.id/artikel/cara-menggunakan-aplikasi-spinning-wheel-names-agar-guru-semakin-kreatif-dalam-mengajar?username=romisaputra Sobur, A. (2017). Filsafat Komunikasi. Remaja Rosdakarya. Sugiyono. (2018). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif dan R&D. Alfabeta. Suherman. (2016). Buku Saku Perkembangan Anak. EGC. Sumitra, A., Windarsih, C. A., Elshap, D. S., & Jumiatin, D. (2020). Meningkatkan Kemampuan Mengenal Huruf Pada Anak Usia Dini Melalui Metode Bercerita Menggunakan Boneka Jari. Tunas Siliwangi : Jurnal Program Studi Pendidikan Guru PAUD STKIP Siliwangi Bandung, 6(1), 1–5. https://e-journal.stkipsiliwangi.ac.id/index.php/tunas-siliwangi/article/view/1487 Supriatin, S., & Wismanata, M. R. (2023). Aplikasi ABC 5 Dasar Berbasis Website Untuk Meningkatkan Kosakata Anak. Pseudocode, 10(1), 12–20. https://doi.org/10.33369/pseudocode.10.1.12-20 Syamsiyah, N., & Hardiyana, A. (2021). Implementasi Metode Bercerita sebagai Alternatif Meningkatkan Perkembangan Bahasa Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(3), 1197–1211. https://doi.org/10.31004/obsesi.v6i3.1751 Trinova, Z. (2012). Hakikat Belajar Dan Bermain Menyenangkan Bagi Peserta Didik. Al-Ta Lim Journal, 19(3), 209–215. https://doi.org/10.15548/jt.v19i3.55 Ulya, A. I. (n.d.). Pengembangan Media Pembelajaran Game Spinning Wheel Berbasis Model 4d Pada Materi Pelajaran Alat Panca Indera. In Lib. Unnes. Ac. Id. UNNES. Wahyundari, N. W. S., & Handayani, D. A. P. (2021). Meningkatkan Kemampuan Berbahasa Lisan pada Anak Usia Dini Melalui Media Gambar Berseri. Jurnal Pendidikan Anak Usia Dini Undiksha, 9(1), 80. https://doi.org/10.23887/paud.v9i2.36877 Wahyuni, M. P. N., & D. (2023). New vision for education: unlocking the potential of technology. VOCEDplus.